Hubungan Individu, Organisasi, Psikologis Petugas Terhadap Keterlambatan Pengembalian Rekam Medis Rawat Inap - Vestine, Veronika; Purbaningrum, Ajeng; Santi, Maya Weka; Ardianto, Efri Tri (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
The return of medical records is the process of returning patient medical records to the medical records department after being used in healthcare services. In 2023, it was found that 42% of inpatient medical records were returned on time but were incomplete, while 32% were delayed for more than 2 x 24 hours. The aim of this study is to analyze the relationship between individual, organizational, and psychological factors of staff and the delay in returning inpatient medical records at Al Huda Hospital, Banyuwangi. Data collection techniques include questionnaires and observation. The population consisted of 101 staff responsible for returning inpatient medical records, with a sample of 80 staff members. This study uses an analytical quantitative method with a cross-sectional approach and chi-square test. Bivariate analysis results showed no relationship between individual factors (knowledge) and organizational factors (leadership). However, there was a significant relationship with psychological factors (attitude) with a Sig. value of 0.001. The researcher suggests that the hospital conduct regular evaluations and provide socialization to staff regarding the return of inpatient medical records and improve staff skills and knowledge on the medical record return procedure.